KREATIVITAS DALAM MEMECAHKAN MASALAH GEOMETRI BANGUN RUANG SISI DATAR SISWA KELAS VIII SMPN 1 ARJOSARI KABUPATEN PACITAN TAHUN PELAJARAN 2013/2014 DITINJAU DARI GAYA KOGNITIF DAN GENDER - Putri, Ariska Yuliana; Riyadi, Riyadi; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aim of this research was to describe male and female students creativity of class VIII SMPN 1 Arjosari District of Pacitan that has a Field Dependent and Field Independent cognitive style in solving space geometric problem. This was a qualitative research. These subjects were taken using purposive sampling and snowball sampling. The subjects of this research were the students in the eight grade of SMPN 1 Arjosari. Data collection techniques in this research were GEFT, creativity test and interview. Techniques to validate the data were time triangulation. The data analysis technique used was the concept of Miles and Huberman consisted of data reduction, data display, and conclusion. The aspect of creativity in this research were consists ofÂ four aspects, there were fluency,Â flexibility, originality and elaboration. Students less creative if they do not meet the four aspects of creativity, quite creative if they meet one, two and three aspects of creativity and creative if they meet the four aspects of creativity. The results showed that male students that have Field Dependent in solving problems are quite creative because they meet one of the creativity aspects which is fluency. The male students that have Field Independent in solving problems are quite creative because they meet two creativity aspects which are fluency and elaboration. The female students that have Field Dependent in solving problems are quite creative because they meet two creativity aspects which are fluency and elaboration. The female students that have Field Independent in solving problems are quite creative because they meet three creativity aspects which are fluency, flexibility and elaboration. So the male and female students that have Field Dependent and Field Independent have a quite creative but it are different in each aspect of creativity.Keywords: creativity, problem solving, cognitive style, gender.